For wireless LAN application, microstrip patch antenna design in S-band - Md. Sohel Rana; Md. Soriful Islam Sourav; Md. Abdulla Al Mamun; Omer Faruk; Md. Mominur Rahaman; Md. Shehab Uddin Shahriar; Sukanto Halder; Md. Toukir Ahmed; Imran Chowdhury; Omar Faruq; Saikat Mondal; Md. Hasibul Islam; Shubhra Kanti Sinha Shuva (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
This article presents a 3.5 GHz rectangular microstrip patch antenna (RMPA) designed, studied, and analyzed for wireless LAN applications. Using Fr-4 as substrate material, whose dielectric permittivity is 4.3, patch thickness is 1.65 mm, and loss tangent is 0.025. A feeding line with an impedance of 50 Ω is utilized to supply the antenna with power. Computer simulation technology (CST) software has been used to design the antenna and origin pro software has been used to display the resulting figures from the simulation. The antenna simulation showed that the return loss is -56.82 dB; the directivity gain is 6.02 dBi, the bandwidth is 0.148 GHz, and the voltage standing wave ratio (VSWR) is 1.0028. The paper aims to increase the return loss, develop a standard VSWR, increase the directivity gain of the antenna, and improve the antenna bandwidth. The results of the proposed antenna were much better than previously published papers, which were suitable for wireless applications. This proposed antenna can be used for future wireless LAN applications.